"Exploring The Socio-Political Constructs Of Motherhood And Female Infertility Through Rohini Rajgopal’s ’What A Lemon Squeezer Doing In My Vagina?’" - Priyanka Naik Dessai (Educational Administration: Theory and Practice, 2024)
This research paper examines the socio-political constructs of motherhood and female infertility as portrayed in Rohini Rajgopal’s novel, "What a Lemon Squeezer Doing in My Vagina?" Utilizing a blend of feminist literary criticism and socio-political analysis, the study delves into how cultural narratives both shape and reflect the stigmatization and challenges associated with female infertility. The novel’s unique narrative approach, characterized by a mixture of humor and stark realism, provides a critical lens through which societal expectations and the often-overlooked struggles of infertile women are explored. This paper highlights the intersection of literary expression and socio-political discourse, offering insights into the complex dynamics between cultural narratives and personal experiences of infertility. The analysis aims to contribute to the broader discourse on gender, identity, and reproductive rights, challenging traditional perspectives and advocating for a more inclusive and empathetic understanding of motherhood.